Synthesis and characterization of high performance CaZrO3-doped X8R BaTiO3-based dielectric ceramics. Issue 7 (August 2015) - Li, Lingxia; Yu, Jingyang; Liu, Yaran; Zhang, Ning; Chen, Junxiao
Abstract: A novel system of lead-free X8R BaTiO3 -based dielectric materials with high dielectric constants was prepared via conventional mixing method. The phase structure, dielectric and electrical properties and the "relaxorlike" characteristic of ceramic materials were systemically studied. The XRD results indicate that no secondary phase formed in the CaZrO3 -doped samples after sintering. SEM micrographs reveal that the grain size of CaZrO3 -doped BaTiO3 -based samples are not uniform, ranging from 0.2 to 0.9 µm. Bulk densities and dielectric properties were measured as a function of CaZrO3 concentration. The Curie temperatures of all CaZrO3 doped samples increase due to the existence of an internal stress between grain cores and shells caused by the diffusion of CaZrO3 . The oxygen vacancies have a profound effect on the dielectric loss and frequency characteristics. The 3.5 wt% CaZrO3 -doped sample sintered at 1250 °C showed the optimal dielectric performance ( ε r =4330, tan  δ <1.5%, Δ C / C 20 °C ≤±14%) that satisfied EIA-X8R specification.